(untitled) (Journal of the College of Basic Education, 2022)
International public relations is the link between the institutions of one society and between other societies, by providing services, ideas and goods to them.In recent years, it is noted that there has been an increase in interest in international public relations and an increase in the demand of international commercial companies to rely on them entirely in order to promote and market their services and products of various kinds, and in different origins and places of production, in addition to that these companies mainly aim to build a good and kind mental image of them among their international audiences.